Mathematical multiple representation and mathematical problem-solving abilities of junior high school students employing an open-ended strategy - Yusnita, Nora; Firmansyah, Firmansyah; Zahari, Cut Latifah; Destini, Rita (Mahesa Research Center, 2025)
This study investigates the effect of the open-ended learning strategy on students’ multiple mathematical representation and problem-solving abilities in junior high school mathematics. A quasi-experimental method employing a pretest–posttest control group design was implemented with two classes of eighth-grade students at SMP Negeri 28 Medan. The experimental group received open-ended learning, while the control group received direct instruction. Data were collected through tests of multiple mathematical representation and problem-solving ability, complemented by classroom observations. Quantitative data were analyzed using descriptive statistics, the Mann–Whitney U test, the independent samples t-test, and Spearman’s rank correlation.The results revealed that students taught using the open-ended learning strategy achieved higher posttest scores in both multiple representation and problem-solving abilities compared to those taught through direct instruction. A statistically significant difference was found in problem-solving ability (p = 0.001), while representational ability showed a positive but nonsignificant trend. Moreover, a significant positive correlation (r = 0.367, p = 0.003*) was found between students’ multiple representation and problem-solving abilities. These findings indicate that open-ended learning promotes higher-order thinking by enabling students to explore diverse solution strategies, construct meaning through multiple representations, and engage in reflective reasoning. The study highlights the pedagogical potential of open-ended learning as an effective approach to fostering conceptual understanding and creative mathematical thinking aligned with the goals of the Merdeka Curriculum.